Astrid the Astronaut: The Astronomically Grand Plan - Book 1 - Neal, Rie; Shipman, Talitha (New York : Aladdin, 2022)
Astrid is excited about her upcoming first year of Shooting Stars, a club dedicated to all things space, but now that her best friend Hallie is more interested in art Astrid is not sure her goal of becoming an astronaut will happen without her friend.
Junior Library Guild
Ages 7-9.
Grades 2-4.
A Junior Library Guild selection
Keywords: Clubs -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Clubs -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Clubs -- Fiction; Friendship -- Fiction; School stories; School fiction